Child of the Fighting Tenth : on the frontier with the Buffalo Soldiers - Hooker, Forrestine C. (Forrestine Cooper), 1867-1932 (OUP E-Books., 2003)
A memoir detailing the frontier childhood and young adulthood of the daughter of Charles Cooper, one of the officers in the Tenth U.S. Cavalry.